Willow Project: The Effect on the Environment and Global Reaction - Dellia Sophy Destary; Nazwa Nurahmania; Nur Sahirah Larasati; Hardi Alunaza; Yusawinur Barella (Al-Musthalah: Jurnal Riset dan Penelitian Multidisiplin, 2024)
There are many other kinds of non-renewable energy sources, however petroleum is one source of energy that is crucial for all nations worldwide. Petroleum is used in many different things these days, including cars, buildings, and home appliances. But because there is a finite amount, different nations must use different approaches to get this energy. A major country, like the United States, definitely needs to use a lot of petroleum energy, which means that a lot of petroleum supply is also needed. The Willow Project, an oil drilling venture in Alaska by ConocoPhillips, was likewise approved by the US. However, because to its detrimental effects on the environment, this project has come under fire from a number of nations and environmental organizations. Using data from libraries and internet searches, the author will talk about the project's effects along with responses from around the globe as well as how it affects the United States.